Prevalence of colonization by Streptococcus agalactiae among pregnant women in Bukavu, Democratic Republic of the Congo - Mitima, Kashosi T; Ntamako, Steve; Birindwa, Achippe M; Mukanire, Ntakwinja; Kivukuto, John M; Tsongo, Kibendelwa; Mubagwa, Kanigula (The Journal of Infection in Developing Countries, 2014)
Introduction: Maternal vaginal colonization by Streptococcus agalactiae (GBS) has an important impact on neonatal health but has not been studied in the Democratic Republic of Congo. The aim of this study was to determine its frequency and influencing factors. Methodology: Vaginal samples (n = 509) for bacteriological analysis were collected from women in Bukavu, eastern DR Congo, during their third trimester of pregnancy, along with information about age, education and socio-economic status, and medical and obstetric-gynecological history. Results: The overall GBS colonization rate was 20%. Colonization was significantly associated with low education, history of urinary infection during the pregnancy, history of premature childbirth or abortion, and HIV-positive serology, but was not significantly associated with socio-economic level or parity. Conclusions: The GBS colonization rate is similar to that found elsewhere on the continent. Further studies, with follow-up of neonates of infected mothers and evaluation of prevention/treatment strategies, are needed.